4th CONSOLIDATED PARTISAN CAVALRY REGIMENT IN THE BATTLES IN STAVROPOL REGION IN OCTOBER - NOVEMBER 1942 - A. Kartashev (Гуманитарные и юридические исследования)
The article is devoted to an insufficiently studied issue of the participation of partisan detachments of the Stavropol Territory in the hostilities of the 4th Guards Kuban Cossack Cavalry Corps against the Nazi invaders in October - November 1942. Based on the journal of military operations of the 10th Guards Kuban Cavalry Division, award documents of partisans, materials from the funds of the State Archives of the Stavropol Territory about the partisan movement in the Stavropol Territory during the Great Patriotic War, memoirs of participants in battles and battles and other sources, the article analyzes the facts concerning the formation of the 4th consolidated partisan cavalry regiment. Its structure, manning, the conditions for joining the named division and the reasons for leaving it are considered, the course of hostilities and their results are described, examples of courage and heroism, the facts of the death of partisans are given. This topic touches upon such a rare phenomenon during the Great Patriotic War, as the entry of a consolidated partisan regiment as a military unit into a cavalry division of the Red Army to solve tasks unusual for partisan formations. The regiment existed for a relatively short period. Having lost their first commander, despite the decision to withdraw from the division, the partisans were forced to participate in bloody battles for the village of Achikulak, where they again suffered heavy losses. The analysis showed the complex nature of the joint use of heterogeneous forces subordinate to the military command and the local civilian leadership, the desire of the partisans to withdraw from the active army to operate behind enemy lines in accordance with their mission.